INFLUENCE OF URTICA DIOICA SEED EXTRACTS ON ACUTE EXPERIMENTAL HEPATOTOXICITY IN VIVO: ANTIOXIDANT AND ANTIHEPATOTOXIC EFFECT - Kulevanova, S.; Panovska, T. K.; Bogdanova, M. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Urtica dioica is an annual herb that belongs to the family Urticaceae. It is known in traditional therapy as acute diuretic, natriuretic and hypotensive. Different parts of this plant have also been used in the treatment of hypertension, stimulation of proliferation of human lymphocytes, immunostimulation on neutrophilis, beneficial effect on the prostate tissue and antirheumatic effects. The aim of the present study was to investigate a possible prophylactic effect of Urtica dioica seed extracts pre-treatment on prevention of oxidative stress generated by CCl4 in rats. A dose of 25 mg/kg of Urtica dioica extracts was administered i.p. to the test groups of female Wistar rats. The positive control group received CCl4 and the negative control group received normal saline. In this investigation the level of lipid peroxidation and serum liver enzyme activities were measured. Histopathological examinations were also carried out. The CCl4 treatment of rats increased the lipid peroxidation and liver enzymes, and also decreased the antioxidant enzyme levels (superoxide dismutase, catalase, glutathione peroxidase and the levels of glutathione). Pre-treatment of the experimental animals with Urtica dioica extracts for 7 days decreased the elevated lipid peroxidation and liver enzyme levels and also increased the reduced antioxidant enzyme levels. Histopahtological studies provided supportive evidence for the biochemical analysis. The present study has shown that Urtica dioica pre-treatment diminishes oxidative stress in the liver generated by applying CCl4. This finding suggests that Urtica dioica has a cell protection effect against oxidative stress in rats.